The Frequency of Enteroaggregative Escherichia Coli and Important Virulence Genes Isolated from Children with Diarrhea - Tahereh Alipour; Farkhondeh Poursina (مجله دانشکده پزشکی اصفهان, 2021)
Background: Enteroaggregative Escherichia coli (EAEC) has recently been identified as the cause of epidemic and endemic chronic watery diarrhea worldwide, especially in developing countries. The aim of this study was to determine the frequency of this strain and its important virulence genes in diarrhea samples.